Significance of halal product, halal certification and management systems in industries and their challenges - Ali, Muhammad Qasim; Noormazlinah, Ahmad; Solehah, Shamsuddin (Yayasan Bhakti Masyarakat Ekonomi Syariah, 2024)
The halal principle is of utmost importance within the Muslim global economy, and halal certification has become increasingly crucial for food and pharmaceutical industries operating in Muslim-majority countries or targeting Muslim consumers globally. The growing concern about safety, hygiene, and quality of food and drinks has enhanced the global appeal of halal products. These products have been made in accordance with Islamic dietary laws and are becoming more prevalent among Muslim and other religious consumers. This study examines the obstacles Malaysia had also confronted in trying to implement halal food and products, and how halal certification may serve as a valuable advertising tool for companies, despite some consumer skepticism. It also investigates the references to Muslim consumers’ wisdom about halal food and products, discovering that halal certification and awareness positively influence purchase intentions. Furthermore, the study provides a framework for investigating factors such as track and trace, and capital adequacy, quality control, trust, and responsibility that affect the authenticity of the halal food chain and Islamic market research. It is noted that halal and Islamic marketing reaches farther than food to other market segments such as medicine and cosmetics. The article explores the role of the Importance of Halal Certification and Management Systems in Industries and the obstacles that businesses face in obtaining halal certification and navigating the complex landscape of halal regulations and standards.